Lives and Livelihoods : Estimates of the Global Mortality and Poverty Effects of the COVID-19 Pandemic - Decerf, Benoit; Ferreira, Francisco H.G.; Mahler, Daniel G.; Sterck, Olivier (Elsevier, 2021)
We evaluate the global welfare consequences of increases in mortality and poverty generated by the Covid-19 pandemic. Increases in mortality are measured in terms of the number of years of life lost (LY) to the pandemic. Additional years spent in poverty (PY) are conservatively estimated using growth estimates for 2020 and two different scenarios for its distributional characteristics. Using years of life as a welfare metric yields a single parameter that captures the underlying trade-o between lives and livelihoods: how many PYs have the same welfare cost as one LY. Taking an agnostic view of this parameter, we compare estimates of LYs and PYs across countries for different scenarios. Three main findings arise. First, we estimate that, as of early June 2020, the pandemic (and the observed private and policy responses) had generated at least 68 million additional poverty years and 4.3 million years of life lost across 150 countries. The ratio of PYs to LYs is very large in most countries, suggesting that the poverty consequences of the crisis are of paramount importance. Second, this ratio declines systematically with GDP per capita: poverty accounts for a much greater share of the welfare costs in poorer countries. Finally, a comparison of these baseline results with mortality estimates in a counterfactual herd immunity scenario suggests that welfare losses would be greater in the latter in most countries.